IMPLEMENTASI KEBIJAKAN TRANSAKSI NON TUNAI DI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG - Natta Sanjaya Natta Sanjaya; Putri Utami Fauzie Putri Utami Fauzie (NIAGARA Scientific Journal, 2018)
The non-cash transaction policy is Presidential Instruction Number 10 of 2016, regarding actions to prevent and eradicate corruption that are being followed up by the parties Ministry of Home Affairs by issuing circular letter SE910/1866/SJ which obliges the Regional Government to carry out non-cash transactions. One of them in Office of Public Works and Spatial Planning Banten Province. The purpose of this research is to find out how the non-cash transaction policy is implemented in the Department Banten Province Public Works and Spatial Planning. Based on the results of research that carried out at the Office of Public Works and Spatial Planning has carried out the transaction with non-cash, but due to the policy of non-cash transactions this is new policy, so the implementation is gradual because there are still a number of transactions that are made in cash. In this study, researchers used research methods descriptive qualitative. In collecting data the researcher made observations with visited the research location and interviewed several parties, such as: the treasurer general office, assistant treasurer, official implementing technical activities and third parties who related to find out how the implementation of non-cash transaction policies in the Office Banten Province Public Works and Spatial Planning. Conclusion of this research the non-cash transaction policy has been implemented in stages. Suggestions from research This is so that non-cash transactions can be carried out better so that every transaction can done in cashless.